Development of innovative behaviors Android application and website for teachers using the waterfall method - Tanuwijaya, Evan; Kurniawan, Jimmy Ellya; Rahmawati, Kuncoro Dewi (Jurnal Inovasi Teknologi Pendidikan, 2024)
This research explores the pivotal role of innovation in education, particularly in response to the COVID-19 pandemic. It focuses on developing the Guru Inovatif Android app and website to enhance educators' innovative teaching practices. These platforms feature a survey to assess innovation levels and training modules to develop innovative skills, aiming to revolutionize teaching methodologies. (In this research, the waterfall methodology is employed, which is used to develop software from start to finish. This model involves a sequential design process, where progress flows in one direction through phases such as requirements, design, implementation, verification, and maintenance. It is utilized to create both an Android-based application and a Laravel-based website.) Testing involved 109 teachers from various educational levels across six regions in Java. Data were collected via a structured Likert-scale survey and analyzed for usability and satisfaction. Results indicated high user-friendliness (4.43) and satisfaction (4.28) but highlighted the need for design consistency (2.37) and error reduction (2.27). By addressing these issues, the Guru Inovatif platforms can better support educators in adopting innovative teaching practices.